Lo inconsciente en la explicación social - Bevir, Mark (2011)
“The Unconscious in Social Explanation”. The proper range and contentof the unconscious in the human sciences should be established by referenceto its conceptual relationship to the folk psychology that informs the standardform of explanation therein. A study of this relationship shows that humanscientists should appeal to the unconscious only when the language of theconscious fails them, that is typically when they find a conflict between people’sself-understanding and their actions. This study also shows that human scientistsshould adopt a broader concept of the unconscious than the one developedby Freud, that is, one free from his ahistorical concept of the instincts and hisahistorical emphasis on the sexual experiences of childhood. The unconscious,understood in this way, has an ambiguous relationship to more recent linguisticand narrativist strands of psycho-analysis.